2020
DOI: 10.3390/biom10091267
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Cathelicidin CRAMP Augments Platelet Activation during Psoriasis in Mice

Abstract: Platelet-associated complications including thrombosis, thrombocytopenia, and haemorrhage are commonly observed during various inflammatory diseases such as psoriasis. Although several mechanisms that may contribute to the dysfunction of platelets during inflammatory diseases have been reported, knowledge on the primary molecules/mechanisms that underpin platelet-associated complications in such conditions is not fully established. Here, we report the significance of the mouse antimicrobial cathelicidin, mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 50 publications
(71 reference statements)
1
9
0
Order By: Relevance
“…Recently, antimicrobial peptides and proteins (AMPs) such as cathelicidin, β-defensins, and S100 proteins, secreted by keratinocytes are inferred to be related with severity of psoriasis lesions ( 21 ), and excessive production of AMPs are widely confirmed in psoriasis lesions ( 21 23 ). Previous studies have indicated that imiquimod increase the production of AMPs ( 24 26 ). Therefore, our experiments were exerted to demonstrate the effect of hyperforin on the expression of AMPs.…”
Section: Resultsmentioning
confidence: 98%
“…Recently, antimicrobial peptides and proteins (AMPs) such as cathelicidin, β-defensins, and S100 proteins, secreted by keratinocytes are inferred to be related with severity of psoriasis lesions ( 21 ), and excessive production of AMPs are widely confirmed in psoriasis lesions ( 21 23 ). Previous studies have indicated that imiquimod increase the production of AMPs ( 24 26 ). Therefore, our experiments were exerted to demonstrate the effect of hyperforin on the expression of AMPs.…”
Section: Resultsmentioning
confidence: 98%
“…While the modulatory effects of ANXA1 and ANXA1 Ac2-26 during inflammation have been extensively studied in numerous disease models, their importance in platelet-mediated thromboinflammation is not yet fully understood. Recently, we reported the significance of FPRs and some of their ligands such as an antimicrobial peptide, LL37 [ 20 , 21 ], and a bacterial formyl peptide, fMLF [ 22 ], in the regulation of platelet function. Due to the critical roles of platelets at the interface between thrombosis and inflammation [ 3 ], the detailed characterisation of inflammatory receptors such as FPR2/ALX will pave the way to the development of novel therapeutic strategies to control exacerbated thromboinflammatory responses during pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, autoimmune patients have impaired tolerance and are at higher risk for developing cardiovascular disease ( 44 ) suggesting potentially shared pathophysiology. Among the self-antigens of interest, we focused our work on LL-37, a T cell autoantigen in psoriasis and SLE ( 11 14 ), that plays a role in innate immune responses as damage-associated molecular pattern (DAMP) ( 45 ) as well as its participation in thrombus formation ( 19 ), both key elements of ACS. Increased LL-37 expression by intermediate monocytes in single-cell RNA sequencing assay of PBMCs was recently demonstrated in acute MI ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is a component of neutrophil extracellular traps (NETs) that are implicated in atherogenesis ( 16 , 17 ). In addition, NET burden is associated with infarct size in ST segment elevation myocardial infarction (STEMI) ( 18 ) while LL-37 is associated with platelet activation and thrombosis ( 19 ). LL-37 is an immune modulator that has HLA-specific or adjuvant effects on the immune response ( 11 , 20 ).…”
Section: Introductionmentioning
confidence: 99%